ANALISIS TERMODINAMIKA SISTEM HIBRIDA PV/T BERDASARKAN MODEL TERMAL - Dadan Hamdani; Yuki N Nasution (PROSIDING SEMINAR KIMIA, 2013)
In this paper, the analysis of PV/T system with air collector have been done as an attempt to investigate the system performances based on energy and exergy analysis using thermodynamics (thermal) analysis. The experimental data for a typical day of July, 9 th 2012 for Bontang City, East Kalimantan are used for calculation of the energy, exergy, energy and exergy efficiencies of the PV and PV/T systems. It is found that varies flow of energy (thermal and electrical) from a minimum of 312 W to maximum of 522 W, the PV exergy varies from a minimum of 18 W to a maximum of 41 W corresponding to the total energy of system and PV/T exergy varies from a maximum of 117 W to a minimum of 52 W, respectively. Meanwhile, the exergy efficiency for the PV/T system varies from a maximum of 18% to a minimum of 12% and exergy efficiency for the PV system varies from a minimum of 3% to a maximum 6%.